2019
DOI: 10.1038/s41598-019-46943-w
|View full text |Cite
|
Sign up to set email alerts
|

Wood properties of Carapa guianensis from floodplain and upland forests in Eastern Amazonia, Brazil

Abstract: The variable environmental conditions of the Amazon forest can affect the wood properties of the tree species distributed across its diverse phytophysiognomies. Carapa guianensis (Andiroba) occurs in upland and floodplain forests, and the wood and oil of its seeds have multiple uses. The aim of this study was to evaluate the wood properties of C. guianensis trees in upland and estuarine floodplain forests of the Amazon River. Eight trees were selected, with four be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
(39 reference statements)
2
7
0
Order By: Relevance
“…This was probably due to beginning of cambial maturation. This trend of increasing specific gravity was also reported by Mohamad and Marsoem (2007) on Acacia auriculiformis wood and Firmino et al (2019) on Carapa guianensis wood. But the opposite results were obtained from the study of Kojima et al (2009) in Gmelina arborea species.…”
Section: Green Specific Gravitysupporting
confidence: 87%
See 2 more Smart Citations
“…This was probably due to beginning of cambial maturation. This trend of increasing specific gravity was also reported by Mohamad and Marsoem (2007) on Acacia auriculiformis wood and Firmino et al (2019) on Carapa guianensis wood. But the opposite results were obtained from the study of Kojima et al (2009) in Gmelina arborea species.…”
Section: Green Specific Gravitysupporting
confidence: 87%
“…In addition, an increase in fiber length was also reported by Darmawan et al (2013) on the initial growth of Perhutani short rotation teak and loJayacal teak from community forests, as well as by Kojima et al (2009) on Gmelina arborea trees. This pattern was similar to the characteristics of juvenile wood which was characterized by short fibers (Gryc et al 2011) and experiences a progressive increase coincide with trees age until they reached a constant fiber length (Lachenbruch et al 2011, Firmino et al 2019. This showed that at the age of eight years, JUN teak trees still produced juvenile wood until they reach a constant fiber length.…”
Section: Fiber Lengthsupporting
confidence: 76%
See 1 more Smart Citation
“…In both clones, there was a tendency for the thickness of the fibre cell walls to increase in the pith-bark direction along the entire tree trunk. These results are considered to be the common variation pattern for fibre cell wall thickening according to Firmino et al (2019). However, according to Baldin et al (2017), it is not possible to define a general trend of radial fibre wall thickness variation since although there is an increase between heartwood and peripheral heartwood, there is a reduction in the thickness of the cell wall in the sapwood.…”
Section: Fibre Dimensionsmentioning
confidence: 99%
“…It is found in upland forests and floodplains, reaching heights up to 40 m (Firmino et al . 2019). This tree has economic importance and multiple uses: the wood is highly valued for products such as furniture, construction, veneers, and plywood, as well as in medicinal applications.…”
Section: Introductionmentioning
confidence: 99%